The Influence of Brand Image, Brand Awareness, and Promotional Strategies on Purchase Intention Decisions and Its Impact on Purchasing Decisions Among Gen Z (Study on Digital Out of Home Advertising: Videotron) - Nabilah Afifah Rasya; Osly Usman; Muhammad Fawaiq (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
With a focus on digital out-of-home advertising, this research seeks to expand on existing information by examining the effects of brand image, brand awareness, and promotional techniques on consumer buy intentions and their influence on Gen Z purchasing decisions. Videotron. Gen Z residents of DKI Jakarta are the target group for this kind of study, which is quantitative in nature and uses an online survey questionnaire. Purposive sampling was the method employed, and there were 228 responders in the sample overall. Tests for validity and reliability as well as hypothesis testing utilizing structural equation modeling (SEM) and SmartPLS software were the analysis methods employed to process the data that was gathered. Through these analysis techniques, the results show that all indicators in the test are valid and reliable, in other words, indicators that are not valid and reliable are not used in further tests, and brand awareness variables and promotional strategies have a significant effect on purchase intentions, then brand image variables have an insignificant effect on purchase intentions, brand image variables and brand awareness have an insignificant effect on purchasing decisions, then promotional strategies have a significant effect on purchasing decisions, brand image variables have an insignificant effect on purchasing decisions through purchase intentions, and brand awareness variables and promotional strategies have a significant effect on purchasing decisions through purchase intentions.